Interpretive Journalism - Salgado, Susana (2019)
Interpretive journalism has been defined in extant research as a style of news reporting that is opposed to descriptive journalism. Rather than simply describing what happened and providing source-driven and fact-focused accounts, it provides journalistic interpretation and analysis through explanations, evaluations, contextualizations, or speculations by the journalist. The prominent role of the journalist in news coverage is linked to the disbelief in value-free facts and in interest-free sources, thus making it necessary to explain the context and interpret the relevance and impact of facts, events, and statements.